Pengaruh Dimensi Fraud Hexagon terhadap Perilaku Kecurangan Akademik - Fauziyah, Rezy; Rahmi, Elvi (Jurnal Ecogen, 2024)
This study aims to analyze was to determine the extent to which the dimensions of the hexagon fraud affect colleger academic fraud. Research surveys using quantitative methodologies are the types of research that are used.  The population in this research are college from Universitas Negeri Padang's Faculty of Economics and Business. Non-probability sampling is the technique used to collect samples. Methods for collecting data with a g-form questionnaire. The data analysis technique used is a quantitative technique.  The results showed that research indicate that academic fraud  colleger at Universitas Negeri Padang's Faculty of Economics and Business are influenced by stimulus and capacity. Conversely, opportunity, rationalization, and collusion have no impact on academic fraud colleger  there, whereas  arrogance has a negative impact on academic fraud colleger